Shiva linga placed on the ruined plinth of a temple - Temples of India Project Team (Jio Institute, 2024)
The Shiva linga (aniconic representation of Shiva) is placed on the ruined plinth of a temple. Open to the sky, this makeshift shrine is highly revered in the Hanuman Garhi temple complex. People are especially seen here performing rituals on a day-to-day basis. The Shiva linga is large and has its own pedestal.